Cell Envelope and Shape of Escherichia coli K12. Crosslinking with Dimethyl Imidoesters of the Whole Cell Wall - Haller, Ingo (1974)
E. coli cells treated with the bifunctional crosslinking reagents dimethyl malonimidate, succinimidate, adipimidate, suberimidate, and sebacinimidate served for the isolation of rod-shaped “ghosts.” These ghosts proved to be crosslinked over their entire surface; i.e., a macromolecule (resistant to boiling 1% Na dodecyl sulfate) the size of the cell had been created. Also, ghosts could similarly be crosslinked. In both cases, the final “sacs” contained about 60-70% protein, and very little or no lipopolysaccharide. When ghosts from which phospholipid had been removed were crosslinked, the covalently closed ghosts were almost pure protein; 80-90% of their dry mass was accounted for by protein. Ammonolysis of the crosslinked material (whether stemming from crosslinked cells or ghosts) showed that the same four proteins (Na dodecyl sulfate gel bands) had been crosslinked that are found in normally prepared ghosts. These observations practically exclude the hypothesis that a fluid mosaic model of membrane structure can be applied to the outer membrane of the E. coli cell envelope; rather, extensive protein-protein interactions must exist over the whole surface of this membrane. These findings are consistent with the possibility that the ghost polypeptide chains are involved in the determination of cellular shape.